2018
DOI: 10.1080/10439463.2018.1553974
|View full text |Cite
|
Sign up to set email alerts
|

Policing nightlife areas: comparing youths’ trust in police, door staff and CCTV

Abstract: Against a background of the pluralisation of policing in contemporary city spaces, and sustained interests in the assessment of policing in the criminology and criminal justice literatures, the current study seeks to draw a comparative analysis in trust between policing actors, as experienced by nightlife consumers. While studies on trust in the police are numerous, this is much less the case for other actors involved in policing urban (nightlife) spaces. Neither is it very well understood how trust is distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Overall, research on citizens' experiences and perceptions of private security is scarce. Existing research includes a few qualitative studies that have focused on the perceptions of individuals, typically young people, who have experienced private policing (Keskinen et al, 2018;Matthews et al, 2000;Morey, 1999;Saarikkomäki, 2016Saarikkomäki, , 2018Wilson et al, 2010) as well as surveys on young people's experiences of security guards and citizen's general perceptions of private security (e.g., Brands & van Doorn, 2018;Fine et al, 2003;Matthews et al, 2000;Moreira et al, 2015;Saarikkomäki & Kivivuori, 2016;van Steden & Nalla, 2010). In addition, ethnographic studies have investigated security guards' work in shopping malls (Manzo, 2004;Wakefield, 2003).…”
Section: Young People and Private Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, research on citizens' experiences and perceptions of private security is scarce. Existing research includes a few qualitative studies that have focused on the perceptions of individuals, typically young people, who have experienced private policing (Keskinen et al, 2018;Matthews et al, 2000;Morey, 1999;Saarikkomäki, 2016Saarikkomäki, , 2018Wilson et al, 2010) as well as surveys on young people's experiences of security guards and citizen's general perceptions of private security (e.g., Brands & van Doorn, 2018;Fine et al, 2003;Matthews et al, 2000;Moreira et al, 2015;Saarikkomäki & Kivivuori, 2016;van Steden & Nalla, 2010). In addition, ethnographic studies have investigated security guards' work in shopping malls (Manzo, 2004;Wakefield, 2003).…”
Section: Young People and Private Securitymentioning
confidence: 99%
“…Issues regarding procedural justice remain underexplored in plural policing literature (O'Neill & Fyfe, 2017;Paek et al, 2019). Perceived fairness and trust in private security has received little research attention, despite indications that youths' perceptions of procedural fairness and their trust in private security are poorer than their perceptions of the public police (Brands & van Doorn, 2018;Saarikkomäki, 2016Saarikkomäki, , 2018. In addition, studies on ethnic minorities' perceptions of procedural justice are scarce.…”
Section: Procedural Justicementioning
confidence: 99%
“…Most well-known, and most relevant for this special issue, is the notion of privatisation, where previously public duties are relinquished wholesale and passed to private entities. Such processes have seen police responsibility for various functions returned to other actors, e.g., monitoring of disorder-based crime to private door staff (see Brands & van Doorn, 2018); the placing of call handling duties to non-police security contractors (see White, 2014); and even the role of police governance to the electorate via police and crime commissioners (see Lister & Rowe, 2015).…”
Section: Diluting Responsibility For Missing Persons: Pluralisation; Responsibilization; Privatisationmentioning
confidence: 99%
“…For instance, the students feared that CCTV could record their sounds and images throughout the campuses, including private areas such as restrooms. Because of these problems, an empirical study in the Netherlands showed that the public tends to trust human supervisors or agents more than agents who monitor surveillance technologies ( Brands and van Doorn, 2020 ).…”
Section: Introductionmentioning
confidence: 99%